Development of the Basic Psychological Needs at School Scale - T.O. Gordeeva; O.A. Sychev (Экспериментальная психология)
The most important factors in the psychological well-being and academic motivation of schoolchildren from the point of view of self-determination theory include the satisfaction of their basic psychological needs. The purpose of the study was to develop a compact questionnaire to measure the satisfaction of three basic psychological needs (autonomy, competence, and relatedness) in middle school students. The study used data from an online survey of 3,901 schoolchildren from different regions of Russia, of which 2,176 (56%) were fifth grade students and 1,725 (44%) eighth grade students. The results of CFA confirmed the expected structure of the questionnaire and demonstrated metric and scalar invariance in the age groups of fifth and eighth graders. Moderate internal consistency of the autonomy satisfaction scale and good internal consistency of other scales were demonstrated. The validity of all developed subscales was confirmed by the correlations of satisfaction and frustration of basic needs with various indicators of academic motivation and psychological well-being. These findings demonstrate that the use of a questionnaire to assess basic psychological needs satisfaction may benefit educational psychologists' efforts to enhance academic motivation and support students' well-being.